N6-isopentenyladenosine dual targeting of AMPK and Rab7 prenylation inhibits melanoma growth through the impairment of autophagic flux - Ranieri, Roberta; Ciaglia, Elena; Amodio, Giuseppina; Picardi, Paola; Proto, Maria Chiara; Gazzerro, Patrizia; Laezza, Chiara; Remondelli, Paolo; Bifulco, Maurizio; Pisanti, Simona (Cell death and differentiation, 2018)
Targeting the autophagic process is considered a promising therapeutic strategy in cancer since a great number of tumors, including melanoma, show high basal levels of protective autophagy that contributes to tumor progression and chemoresistance. Here, exploiting both in vitro and in vivo approaches, we identified N6-isopentenyladenosine (iPA), an end product of the mevalonate pathway, as a novel autophagy inhibitor with an interesting anti-melanoma activity. iPA, after being phosphorylated by adenosine kinase into 5′-iPA-monophosphate, induces autophagosome accumulation through AMPK activation, measured by increased fluorescent GFP-LC3 puncta and enhanced conversion into the lipidated autophagosome-associated LC3-II. However, at a later stage iPA blocks the autophagic flux monitored by p62 accumulation, Luciferase reporter-based assay for LC3 turnover in living cells and fluorescence of a tandem RFP-GFP-LC3 construct. Impaired autophagic flux is due to the block of autophagosome–lysosome fusion through the defective localization and function of Rab7, whose prenylation is inhibited by iPA, resulting in a net inhibition of autophagy completion that finally leads to melanoma apoptotic cell death. AMPK silencing prevents apoptosis upon iPA treatment, whereas basal autophagosome turnover is still inhibited due to unprenylated Rab7. These results strongly support the advantage of targeting autophagy for therapeutic gain in melanoma and provide the preclinical rational to further investigate the antitumor action of iPA, able to coordinately induce autophagosome accumulation and inhibit the autophagic flux, independently targeting AMPK and Rab7 prenylation. This property may be particularly useful for the selective killing of tumors, like melanoma, that frequently develop chemotherapy resistance due to protective autophagy activation.